2001
DOI: 10.1097/00004714-200104000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Diphenhydramine Alters the Disposition of Venlafaxine Through Inhibition of CYP2D6 Activity in Humans

Abstract: CYP2D6 is the major enzyme involved in the metabolism of venlafaxine. Subjects with a low CYP2D6 activity have increased plasma concentrations of venlafaxine that may predispose them to cardiovascular side effects. In vitro and in vivo studies showed that diphenhydramine, a nonprescription antihistamine, can inhibit CYP2D6 activity. Therefore, the authors investigated in this study a potential drug interaction between diphenhydramine and venlafaxine. Fifteen male volunteers, nine with the extensive metabolizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 29 publications
1
42
0
1
Order By: Relevance
“…In a previous case report, the half-life of diphenhydramine was 2-fold greater than the usual value in an elderly woman who had a prolonged half-life of imipramine (Glassman et al, 1985), which is mainly metabolized by CYP2D6 (Koyama et al, 1997), suggesting that diphenhydramine is a substrate of CYP2D6 in vivo. In addition, diphenhydramine is known to inhibit the metabolism of several other CYP2D6 substrates in vitro and in vivo (Hamelin et al, 1998(Hamelin et al, , 2000Lessard et al, 2001;He et al, 2002). These findings, coupled with the results of the present study, suggest that diphenhydramine is not only a potent inhibitor of CYP2D6 but also a high-affinity substrate of CYP2D6 in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In a previous case report, the half-life of diphenhydramine was 2-fold greater than the usual value in an elderly woman who had a prolonged half-life of imipramine (Glassman et al, 1985), which is mainly metabolized by CYP2D6 (Koyama et al, 1997), suggesting that diphenhydramine is a substrate of CYP2D6 in vivo. In addition, diphenhydramine is known to inhibit the metabolism of several other CYP2D6 substrates in vitro and in vivo (Hamelin et al, 1998(Hamelin et al, , 2000Lessard et al, 2001;He et al, 2002). These findings, coupled with the results of the present study, suggest that diphenhydramine is not only a potent inhibitor of CYP2D6 but also a high-affinity substrate of CYP2D6 in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 74%
“…In fact, several classic antihistamines, such as chlorpheniramine, mequitazine, and promethazine, have been shown to be metabolized by CYP2D6 (Nakamura et al, 1996(Nakamura et al, , 1998Yasuda et al, 2001). In addition, previous studies revealed that diphenhydramine inhibited the metabolism of several CYP2D6 substrates in vivo and in vitro (Hamelin et al, 1998(Hamelin et al, , 2000Lessard et al, 2001;He et al, 2002). These findings suggest that the metabolism of diphenhydramine is also mediated by CYP2D6.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Several drugs detected during the routine drug screening are metabolized by CYP2D6. Patients who are CYP2D6 PMs, or are taking drugs that may interact, may receive concentrations in the range of those found in overdose when taking therapeutic doses [20,55]. Thus, drug interactions involving VEN may have occurred in several of the cases included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The SSRIs are twice as effective as the "placebo" effect at reducing menopausal symptoms in randomized clinical trials [138][139][140], so there is naturally an increased usage of SSRIs with long-term tamoxifen treatment to maintain compliance. Unfortunately, the metabolism of tamoxifen to hydroxylated metabolites [141][142][143] and the metabolism of SSRIs [39,[144][145][146][147] both occur via the CYP2D6 gene product. Indeed Stearns and coworkers [97] showed that the SSRI inhibitor paroxetine reduced the levels of endoxifen during adjuvant tamoxifen therapy and endoxifen levels decrease by 64% in women with wild type CYP2D6 enzyme.…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%